Association between early life second-hand smoke exposure on child sleep and psychoactive substance use on adult sleep patterns in an urban informal settlement in Uganda - Solomon T. Wafula; Lydia N. Namakula; John B. Isunju; Richard K. Mugambe; Tonny Ssekamatte; David Musoke; Rhoda K. Wanyenze (PLoS ONE, 2025)
Background Psychoactive substance use in adults and second-hand smoke (SHS) exposure among children are leading contributors to sleeping problems. Despite this, there is limited data on how these exposures influence sleep patterns in informal settings. Our study assessed the associations between substance use, SHS exposure and sleep disturbances among adults and children in an urban informal settlement in Uganda. Methods We conducted a cross-sectional study in an urban informal settlement in Kampala, Uganda. Data was collected on self-reported sleep problems among adults including sleep duration, insomnia and sleep dissatisfaction, as well, as sleep-disordered breathing (SDB) in children. We evaluated children’s early-life SHS exposure and psychoactive substance use in adults using questionnaires. We modelled the associations between the exposures and sleep problems in adults and children using modified Poisson regression. Results Data were collected from 284 adults, who also reported on their children’s sleep experience. Among adults, 59.2% reported insufficient sleep (less than 7 hours), 34.9% experienced insomnia, and 28.3% were dissatisfied with their sleep patterns. Active smoking was associated with insomnia (Prevalence Ratio (PR) = 2.74, 95% Confidence Interval (CI): 1.14–6.59), and alcohol use was associated with sleep dissatisfaction (PR = 1.81, 95% CI 1.23–2.69). In children, 40.0% (88/220) exhibited SDB problems. Those exposed to SHS either during pregnancy or within six months post-birth had a higher risk of SDB than unexposed children (PR = 1.78, 95% CI 1.21–2.61). The risk was also elevated for children exposed to SHS during both periods (PR = 1.48, 95% CI 1.02–2.13). Conclusions Our findings suggest that smoking was associated with insomnia and alcohol with sleep dissatisfaction among adults. Early-life SHS exposure was associated with an increased risk of SDB in children. These results emphasize the need to support ongoing public health initiatives and maintain a smoke-free environment, particularly for children in their early life.